REKONSTRUKSI PEMIKIRAN PENDIDIKAN ISLAM DI ERA DIGITAL: INTEGRASI NILAI SPIRITUAL DAN LITERASI TEKNOLOGI - Fatimah Alhaddad; Asep Rahmatullah (As-Sulthan Journal of Education, 2026)
This paper discusses Abuddin Nata’s thoughts on Islamic education in response to the rapid development of the digital era. The study aims to analyze how Islamic educational concepts can adapt to technological advancement while maintaining spiritual and moral values. This research employs a library research method by examining Abuddin Nata’s works and relevant literature related to Islamic education and digitalization. The results indicate that digitalization offers significant opportunities for Islamic education, including broader access to learning resources, increased effectiveness of teaching methods, and the development of innovative learning media. However, digital transformation also presents challenges, particularly the risk of declining moral values, ethical awareness, and spiritual orientation among learners if technology is used without proper guidance. Abuddin Nata emphasizes that Islamic education should prioritize character building and the internalization of Islamic values alongside the development of digital competencies. Therefore, the integration of spiritual values and digital literacy is essential to ensure that Islamic education remains relevant, balanced, and capable of producing individuals who are intellectually competent, technologically adaptive, and morally responsible in the digital era.